Musculoskeletal changes in aging, prevention and physiotherapy in falls in the elderly: a bibliographic review - Santos, Pedro Rafael Dourado dos (2021)
Aging is a dynamic, progressive and irreversible process and is closely linked to biological, psychological and social factors, the musculoskeletal and bone system is crucial in the aging process, falling is the main external cause of morbidity and mortality among this population worldwide and it is also an indicator of worsening quality of life, Physiotherapy has a very important role both in the prevention of falls and in the rehabilitation of these individuals, using different techniques. The objective of this work was to deepen and analyze the musculoskeletal changes of aging, prevention and physiotherapeutic performance in falls in the elderly. Bibliographic, descriptive research. One of the main signs of aging is the reduced capacity for work activities at work, adaptation to the environment and functional independence. Physiotherapy has a very important role both in the prevention of falls and in the rehabilitation of these individuals, using techniques such as stretching, muscle strengthening, gait and balance training, improvement of proprioception, seeking to maintain or improve functional capacity, reducing disabilities and limitations and providing greater functional independence. This study concluded that with the increasing aging rate and the increase in falls in the elderly population, this study has become of great relevance, as this event can cause serious consequences, reducing autonomy, causing functional dependence and decreased quality of life and Physiotherapy it enters as a strong provider of the best quality of life for this population.